Internalisasi Pendidikan Agama Islam di Tengah Masyarakat Multikultural - Haryono Haryono (JPT : Jurnal Pendidikan Tematik, 2026)
Multicultural society is a social reality characterized by diversity in ethnicity, culture, language, and religion coexisting within the same social environment. This condition requires an educational approach that not only instills religious values but also fosters tolerance, inclusivity, and civility. Islamic Religious Education (IRE) plays a strategic role in addressing these challenges through the internalization of Islamic values in a comprehensive manner. This article aims to examine the concept of internalizing Islamic religious education, the role of IRE in a multicultural context, and the strategies for internalizing Islamic values in social life. This study employs a qualitative library research method by analyzing various relevant sources, including books, scholarly journals, and academic articles. The collected data are analyzed using a descriptive qualitative approach to obtain an in-depth theoretical understanding. The findings indicate that the internalization of Islamic religious education must integrate cognitive, affective, and psychomotor aspects holistically. Islamic religious education developed through contextual approaches, educators’ role modeling, habituation of tolerant attitudes, and open dialogue can effectively shape moderate and inclusive religious perspectives. Therefore, the internalization of Islamic religious education significantly contributes to the formation of individuals who are faithful, possess noble character, and are capable of living harmoniously within a multicultural society.